Risk, uncertainty and monetary policy - Geert Bekaert; Marie Hoerova; Marco Lo Duca (National Bank of Belgium, 2012)
The VIX, the stock market option-based implied volatility, strongly co-moves with measures of the monetary policy stance. When decomposing the VIX into two components, a proxy for risk aversion and expected stock market volatility (“uncertainty”), we find that a lax monetary policy decreases both risk aversion and uncertainty, with the former effect being stronger. The result holds in a structural vector autoregressive framework, controlling for business cycle movements and using a variety of identification schemes for the vector autoregression in general and monetary policy shocks in particular.
Keywords: E44; E52; G12; G20; E32; 330; Monetary policy; Option implied volatility; Risk aversion; Uncertainty; Business cycle; Stock market volatility dynamics; Finanzmarkt; Entscheidung unter Risiko; Risikoaversion; Aktienmarkt; Geldpolitik; Volatilität; USA